Tourism Space: Concept, ‘Dimensions’ and Features - Włodarczyk, Bogdan (Turyzm/Tourism, 2007)
The author identifies and describes the characteristics of tourism space as the main research field in tourism geography. He also attempts to describe the ways tourism space is perceived and to divide it on the basis of selected concepts found in the Polish literature on the subject.